Perlindungan Hukum Terhadap Nasabah Deposito Dengan Bunga Di Atas Yang Diizinkan Otoritas Jasa Keuangan - Syawal Syawal (Nagari Law Review, 2018)
The main factor for the weakness of the customers is the lack of public awareness of the rights. In order to attract more customers, some bank offer higher rate of interest above allowed by Financial Services Authority (OJK) or protected by Saving Guaranty Institution (LPS). The problem is how is the protection to customer in who involves in such agreement. The study was conducted at PT BPR Bharma Pejuang EmpatLima Tanjung Pati District of Lima Puluh Kota. The research method used is empirical juridical approach. The result of this research is that the factors influencing the determination of deposit rates higher than LPS the target of desired profit, competition among other commercial bank and Bank Overhead Cost. In order to avoid any lawsuit, the bank requires the customer to sign a declaration that fund will be kept in even though it is not guaranteed by LPS. Actually there is no legal protection for the customer since the deposit interest rate is not in accordance with the LPS provisions. Let alone the customer has signed the letter that the fund is not guaranteed by LP. It is suggested that OJK and the Deposit Insurance Agency take firm action against BPR that gives interest which are not in accordance with LPS provisions. The customers should be are more careful in saving and not just expect higher profit but ignore the possible risk. The customer should not sign a statement that his fund would not protected by LPS because it will be is detrimental for security deposited funds